Risk Management as a Determinant of Stock Trading Behavior - Halimah, Siti Nur; Alkarim, M.Ghazy; Amelia, Ayu; Afrianty, Nonie (Universitas Dehasen Bengkulu, 2025)
The stock market, or capital market, serves as one of the instruments through which a country can enhance its economic performance. In addition to supporting companies and institutions in securing financing, the capital market also functions as an investment platform for the public. However, since President Prabowo Subianto stated that stock trading for ordinary people is equivalent to gambling, the capital market has come under significant public scrutiny. This study aims to examine the influence of risk management on the stock-trading behavior of fifth-semester students in the Sharia Economics Study Program at the State Islamic University of Fatmawati Sukarno Bengkulu. The research employs a descriptive qualitative approach using purposive sampling and involves 25 respondents. Data were collected through in-depth interviews and analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the application of risk management has a positive effect on students’ stock-trading behavior. Most respondents have implemented strategies such as cut-loss mechanisms and portfolio diversification, and they are able to manage their emotions when facing market fluctuations. However, a small number of students have not applied these practices optimally due to limited experience and financial literacy.